Sociodemographic and metabolic risk characteristics associated with metabolic weight categories in the Women’s Health Initiative - Cordola Hsu, Amber R. (Cardiovasc Endocrinol Metab, 2020)
To identify sociodemographic and metabolic correlates of weight categories in postmenopausal women. METHODS: The Women’s Health Initiative enrolled 161 808 postmenopausal women ages 50–79. We included those free of cardiovascular disease (CVD) and with CVD risk factors and biomarkers (n = 19 412). Normal weight was defined as a BMI ≥18.5 and <25 kg/m(2) and waist circumference <88 cm and overweight/obesity as a BMI ≥25 kg/m(2) or waist circumference ≥88 cm. Metabolically healthy was based on <2 and metabolically unhealthy ≥2 traits: triglycerides ≥150 mg/dl, systolic blood pressure (BP) ≥130 mmHg or diastolic BP ≥85 mmHg or antihypertensives or diuretics, fasting glucose ≥100 mg/dl or diabetes medication, and high-density lipoprotein cholesterol <50 mg/dl. Polytomous multinomial logistic regression with generalized link logit function provided the odds of metabolically healthy normal weight (MHNW), metabolically unhealthy normal weight (MUHNW), metabolically healthy overweight/obese (MHO), and metabolically unhealthy overweight/obese (MUHO) according to demographic and risk factor measures. RESULTS: Among the 19 412 postmenopausal women, 2369 (12.2%) participants had prevalent diabetes. Advanced age was associated with an increased odds of MUHNW as compared with the MHNW after adjusting for covariates [odds ratio (OR) 1.04, P < 0.0001]. Black/African American ethnicity was associated with a decreased odds of MUHNW (OR 0.64, P < 0.0001) and MUHO (OR 0.77, P = 0.0004), while an increased odds for MHO (OR 1.50, P < 0.0001) as compared with White MHNW. CONCLUSIONS: Advanced age and ethnicity are important indicators of metabolic weight categories among postmenopausal women.